PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR DAN KEAKTIFAN BELAJAR SISWA DI SMK NEGERI 1 NGAWEN - Kiki Okta Dwi Utama; Sukaswanto Sukaswanto (Jurnal Pendidikan Vokasi Otomotif, 2020)
This study aims (1) to determine the effect of using the Project Based Learning learning model on learning outcomes in Light Electricity Maintenance subjects at SMK N 1 Ngawen. (2) To determine the effect of the use of Project Based Learning learning methods on learning activeness in the subjects of Maintenance of Electric Vehicle Light in SMK N 1 Ngawen. This research is a quasi experiment with a pretest-posttest Control Group Design research design. The analysis test uses the independent sample T-test and descriptive analysis to describe the learning outcomes data and learning activeness. The results showed that: independent sample t-test on final learning outcomes or post-test obtained t count t table is 2.964 1,670. The significance value of the post-test results 0.004 0.05, then Ho is rejected and Ha is accepted. This means that there is a significant difference between the results of the experimental class post-test with the control class. Then the results of the independent sample t-test on the students activeness obtained the results that t arithmetic t table is 5.543 1.670. Significance value t 0.00 0.05, then Ho is rejected and Ha is accepted. This means that there is a significant difference in student activeness between the control class and the experimental class. Then it can be concluded that there is a significant influence on the project based learning model of learning outcomes learning and learning activeness of class XI students majoring in light vehicle engineering at State 1 Vocational School, Ngawen.